2014
DOI: 10.1007/s13280-014-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

The role the Great Barrier Reef plays in resident wellbeing and implications for its management

Abstract: Improvements in human wellbeing are dependent on improving ecosystems. Such considerations are particularly pertinent for regions of high ecological, but also social and cultural importance that are facing rapid change. One such region is the Great Barrier Reef (GBR). Although the GBR has world heritage status for its 'outstanding universal value', little is known about resident perceptions of its values. We surveyed 1545 residents, finding that absence of visible rubbish; healthy reef fish, coral cover, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Overall, the perceived impacts and risks of LNG development (in particular, dredging operations) to the marine environment within the Port of Gladstone were the most important drivers of local attitudes, explaining the largest proportion of variance in the regression model (Table ). This finding supports the conclusions of recent work by Larson et al (: 166), who found that coastal communities in the GBR “considered [the health of the marine environment] to be more important to quality of life than the jobs and incomes associated with industry”. The significance of this conclusion becomes clearer when we consider the emphasis that is placed on the economic benefits of gas development in public discourse (Schultz and Zelezny, ; Michaud et al , ; Devine‐Wright, ; Gross, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the perceived impacts and risks of LNG development (in particular, dredging operations) to the marine environment within the Port of Gladstone were the most important drivers of local attitudes, explaining the largest proportion of variance in the regression model (Table ). This finding supports the conclusions of recent work by Larson et al (: 166), who found that coastal communities in the GBR “considered [the health of the marine environment] to be more important to quality of life than the jobs and incomes associated with industry”. The significance of this conclusion becomes clearer when we consider the emphasis that is placed on the economic benefits of gas development in public discourse (Schultz and Zelezny, ; Michaud et al , ; Devine‐Wright, ; Gross, ).…”
Section: Resultssupporting
confidence: 90%
“…Stay‐at‐home parents (predominantly women) reported an array of views regarding the benefits of industry in Gladstone, and this may be linked to having partners or spouses in the LNG sector, an area that merits further attention. In general, however, these findings support the conclusions of recent work by Larson et al (), which demonstrated that longer‐term residents of the GBR region are generally dissatisfied with the benefits of industrial development.…”
Section: Resultssupporting
confidence: 89%
“…Similar observations were made by Saltzer (2002) who found that experiencing the beauty of nature, being in a natural place, experiencing an undeveloped environment, water quality, fish, corals, and other marine life are important reasons for visiting the GBRWHA. In a parallel study of residents' perception of key GBRWHA-based values, Larson, Stoeckl, Farr, and Esparon (2014) found environmental factors to be most important to their overall quality of life relative to commercial activities, such as mining, agriculture, and fishing. Indeed, there is ample evidence that the environment has positive influences on well-being and quality of life (Kopmann & Rehdanz, 2013;Vemuri, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Benefits which group together using PCA, with factor loadings in brackets; adapted from Larson et al (2014). this group 'primary plus', noting that this alternate grouping lends similar insights to those discussed in the main body of the paper.…”
Section: Table C1mentioning
confidence: 91%
“…Using PCA to identify separable groups Using Principal Components Analysis (PCA), our importance scores for the 18 benefits assessed in the questionnaire collapsed into 5 factors presented in Table C1. The benefits that load onto the first factor include all of those which grouped together using correlation coefficients, and also undeveloped beaches (see Larson et al (2014) for more detailed analysis). We have thus re-named…”
Section: Appendix Amentioning
confidence: 99%